$x^3-y^3$ $\,=\,$ $(x-y)(x^2+y^2+xy)$

Let’s assume, $x$ and $y$ denote two quantities in algebraic form.

- The subtraction of $y$ from the $x$ is written as $x-y$.
- The subtraction of $y$ cubed from $x$ cubed is written as $x^3-y^3$.
- Add the sum of the squares of $x$ and $y$ to the product of $x$ and $y$, and their addition is written as $x^2+y^2+xy$.

According to the difference of cubes arithmetic property, the subtraction of $y$ cube from $x$ cube is equal to the product of the subtraction of $y$ from $x$ and the addition of the sum of squares of $x$ and $y$ and the product of $x$ and $y$.

$\therefore\,\,\,$ $x^3-y^3$ $\,=\,$ $(x-y)$ $\times$ $(x^2+y^2+xy)$

Now, let us learn much more about the $x$ cube minus $y$ cube algebraic identity.

The $x$ cube minus $y$ cube algebraic identity is alternatively written in the following mathematical form.

$a^3-b^3$ $\,=\,$ $(a-b)(a^2+b^2+ab)$

The $x$ cubed minus $y$ cubed algebraic identity is mainly used in two different cases.

- It is used as a formula to find the difference of cubes of two quantities in basic mathematics.
- It is also used as a formula to express the difference of two quantities in mathematical form as a product of two factors.

The $x$ cube minus $y$ cube algebraic identity can be derived mathematically in two methods.

Learn how to prove the $x$ cubed minus $y$ cubed identity by the algebraic identities.

Learn how to derive the $x$ cube minus $y$ cube formula geometrically by the volume of a cube.

Assume that $x = 3$ and $y = 1$

$(1).\,\,$ $x-y$ $\,=\,$ $3-1$ $\,=\,$ $2$

$(2).\,\,$ $x^2+y^2+xy$ $\,=\,$ $3^2+1^2+3 \times 1$ $\,=\,$ $9+1+3$ $\,=\,$ $13$

$(3).\,\,$ $x^3-y^3$ $\,=\,$ $3^3-1^3$ $\,=\,$ $27-1$ $\,=\,$ $26$

Now, find the product of the $x-y$ and $x^2+y^2+xy$.

$\implies$ $(x-y)$ $\times$ $(x^2+y^2+xy)$ $\,=\,$ $2 \times 13$ $\,=\,$ $26$

It is evaluated that the product of them is equal to $26$, and the difference of cubes of $x$ and $y$ is also equal to $26$.

$\,\,\,\therefore\,\,\,\,\,\,$ $x^3-y^3$ $\,=\,$ $26$ $\,=\,$ $(x-y)(x^2+y^2+xy)$

In this way, you can verify the $x$ cube minus $y$ cube algebraic identity by taking any two numbers.

Latest Math Topics

Aug 31, 2024

Aug 07, 2024

Jul 24, 2024

Dec 13, 2023

Latest Math Problems

Sep 04, 2024

Jan 30, 2024

Oct 15, 2023

Copyright © 2012 - 2023 Math Doubts, All Rights Reserved